Chronic care case management for the frail elderly population in the United States: normative, funding and organizational aspects (Italian Journal of Public Health, 2004)
In the most developed countries, it is necessary to bring about significant changes to health care delivery through the strengthening of prevention, rehabilitation and the integration of the social and healthcare dimensions.This means moving the policy focus from “treating” to “taking care” of the sick in a broader and more integrated way, one which is more closely linked to the World Health Organization’s definition of health as physical, psychological and social well-being. This change involves the delivery of care for the elderly. Developed countries are confronting this issue by using different community-based programs to integrate acute and long-term care services for frail elderly individuals with complex health needs.The objective of this health policy article is to give an overview of the most recent initiatives on long-term care management for the elderly including normative, funding and organizational issues in the USA, as their public health system largely differs from those of the Western European countries.Particular attention is given to the PACE (Program of All Inclusive Care for the Elderly), which applies a comprehensive approach to managing the care of the frail elderly population and would represent a new framework in geriatric care. By incorporating a central core care team to manage the needs of each elderly individual, this approach recognizes the contributing factors that non-traditional health related functions play in the overall health of the individual.Although there is a little knowledge of this program, as it covers a very small percentage of the eligible individuals, and it may be difficult to extrapolate to other sectors of the population, PACE offers many lessons that could be applied to more effective integration of care for individuals and lead to better health outcomes.
Keywords: long-term care management; managed care; elderly people; public health strategies